Barriers and facilitators for caregiver involvement in the home care of people with pressure injuries: A qualitative study. - Francisco José García-Sánchez; Vicente Martínez-Vizcaíno; Beatriz Rodríguez-Martín (PLoS ONE)
Aim To explore the barriers and facilitators perceived by home caregivers regarding their involvement in the home care of people with pressure injuries. Background Although home caregivers are key in the process of caring for people with pressure injuries, little is known about their perceptions regarding their involvement in the same. Methods A qualitative study based on grounded theory involving a theoretical sample of 15 home caregivers of people with pressure injuries within the health district of Puertollano, Spain. Results This study identified three barriers (feminization of care, necessary life adaptations as a home caregiver, and the organization of health services) and three facilitators (the perceived family duty for caring, willingness to provide care, and satisfaction with the care received on behalf of primary care services) associated with caregiver involvement in the home care of pressure injuries. Conclusions The care of a person with pressure injuries is perceived as a duty and requires important adaptations affecting the home caregiver's personal, social and work life. The emotional closeness and trust that develops between a patient and the primary care staff equals an involvement which, in turn, also has positive results for both the home caregiver and the patient.